Design and Fabrication of a Ploughing and Seeding Machine and Its Applications - Babu , V. Ram; Mohan , Ch.; Sandeep , B.; Chandini , B.; Kumar , B. Sudheer; Venkatesh , D. (International Journal of Membrane Science and Technology, 2023)
Agriculture being one of the major livelihoods in India, it is very indispensable to discover and implement new idea in this field though lot of work has been done in this area. It is unfortunate that, these ideas are not been implemented properly in actual field. This is due to high cost and is complicated for rural people. Agro-technology is the technology of agriculture, as the methods or machinery needed for efficient production. Agriculture sector need an improvement in the efficiency of the crop produced and also to develop a better mechanical machine to help the agriculture field which reduces the amount and time of work spent on one crop. Ploughing and seeding processes are fundamental stages in agricultural field, they can impact crop yield and overall farm productivity. Nowadays farmers using bulls for ploughing a crop, it takes lot of time if it is done by farmer and animals. There is another way to plough a field that is by using tractors, but the tractors are very expensive. A farmer cannot effort that much of money. In order to rectify this problem, a power tiller machine has been designed which is capable of doing ploughing and seeding operations simultaneously. This is fabricated with less capital. The electric power tiller machine helps to reduce the time and cost involved in tilling. The development of this ploughing and seeding machine represents a significant step towards a more sustainable and technologically advanced agricultural sector.